A Two‐Week Treatment with Plant Extracts Changes Gut Microbiota, Caecum Metabolome, and Markers of Lipid Metabolism in ob/ob Mice. Issue 17 (25th June 2019) - Brochot, Amandine; Azalbert, Vincent; Landrier, Jean‐François; Tourniaire, Franck; Serino, Matteo
Abstract : Scope: Targeting gut microbiota dysbiosis by prebiotics is effective, though side effects such as abdominal bloating and flatulence may arise following high prebiotic consumption over weeks. The aim is therefore to optimize the current protocol for prebiotic use. Methods and results: To examine the prebiotic properties of plant extracts, two independent studies are conducted in ob/ob mice, over two weeks. In the first study, Porphyra umbilicalis and Melissa officinalis L . extracts are evaluated; in the second study, a high vs low dose of an Emblica officinalis Gaertn extract is assessed. These plant extracts affect gut microbiota, caecum metabolome, and induce a significant lower plasma triacylglycerols (TG) following treatment with P. umbilicalis and significantly higher plasma free fatty acids (FFA) following treatment with the low‐dose of E. officinalis Gaertn. Glucose‐ and insulin‐tolerance are not affected but white adipose tissue and liver gene expression are modified. In the first study, IL‐6 hepatic gene expression is significantly (adjusted p  = 0.0015) and positively ( r  = 0.80) correlated with the bacterial order Clostridiales in all mice. Conclusion: The data show that a two‐week treatment with plant extracts affects the dysbiotic gut microbiota and changes both caecum metabolome and markers of lipid metabolism in ob/ob mice. Abstract : A two‐week plant extract treatment affects gut microbiota and caecum metabolome of ob/ob mice. Furthermore, modulations in plasma triacylglycerols (TG), free fatty acids (FFA), white adipose tissue (WAT), and liver gene expression are reported, depending on extract nature and dose. The data may suggest that the current medical practice surrounding prebiotics should be rethought in order to limit side effects by reducing treatment duration and dose.